ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG BAWANG MERAH DI PASAR INPRES KOTA LHOKSEUMAWE - Cut Fitria; Cut Putri Melita Sari; Tarmizi Abbas; Mutia Rahmah; Mustakim Mustakim (Jurnal Ekonomi Pertanian Unimal, 2022)
This study aims to determine the effect of working hours, capital, sales volume and work experience on the income of onion traders. The data used is primary data with a total of 16 observations. The analytical method used in this study is Ordinary Least Square (OLS). The results of the partial test show that capital and sales volume have an effect on the income of onion traders, while working hours and work experience have no effect on the income of onion traders. Meanwhile, Simultaneously Working Hours, Capital, Sales Volume and Work Experience have a significant effect on the income of Onion traders